The Risks of Unauthorized Practice of Law Charges in the United States When Non-Lawyers Use Legal Software - Rani, Sunita; Bansal, Arpana (International Journal of Psychosocial Rehabilitation, 2021)
This article analyzes the assessment of the United States Court of Appeals for the Ninth Circuit in re: Jayson Reynosa: Frankfort Digital Services et al. v. Sara L. Kastler, United States Trustee et al. (2007). Non-attorneys were accused of unlawful acts of regulation for providing liquidation request administrations through internet-based legitimate programming or master frameworks in regulation laid out for recording insolvency appeal shapes. The United States Court of Appeals for the Ninth Circuit found, in addition to other things, that appellants were liquidation request preparers, not attorneys, who had surpassed their authoritative dispatch by offering legitimate counsel and administrations disregarding California regulation controlling lawful practice and 11 U.S.C. Bunch. 110 of the Bankruptcy Code, while breaking down the legitimate results of non-attorneys involving lawful programming in the course of action of lawful curves (2002).